Thèses sur la reproduction sociale sous le capitalisme - Fischbach, Franck (Bollettino Filosofico, 2025)
The purpose of this article is to distinguish and articulate three forms of reproduction: economic (re)production, social reproduction, and the reproduction of social structures. After defining these different forms of reproduction, the task is to diagnose the state in which each of them finds itself today, as well as the contradictions that arise between them in our contemporary capitalist societies. The article introduces the concept of “ecological reproduction” and focuses on the link between social reproduction and ecological reproduction, showing in particular how a crisis in the latter leads to a crisis in the former. Keywords: Crisis of Reproduction, Ecological Reproduction, Economic Production, Reproduction of Relations of Production, Social Reproduction